Prediction of voltage collapse in electric power systems - Azah Mohamed,; Ghauth Jasmon, (1996)
With the increased loading and exploitation of the power transmission system, the problem of voltage instability and voltage collapse has become a growing concern. Voltage instability of large power systems has been considered as a complex problem due to the large number of power system components participating in the voltage collapse process. As a result, two distinct methods have been adopted for voltage stability analysis, that is, the power flow based static method and the time simulation based dynamic method. This paper analyses the basic mechanism of voltage collapse by using the static and dynamic load models. A newly developed indicator using the line stability factors is proposed with the aim of predicting voltage collapse in transmission networks. The mathematical concept of the line stability factors is explained and the factor which acts as indicator of proximity to voltage collapse is defined such that it varies in the range between 0 (system stable) and 1 (voltage collapse). The line stability factors are easily calculated and uses information of a normal load flow. Tests carried out by using the line stability factors as indicators of proximity to voltage collapse illustrate the advantages and simplicity of using the factors. The prediction of voltage collapse caused by a uniform increase of the load as well as due to other contingencies such as line outage and step increase in mechanical load, is accurately obtained by using the line stability factors